ANALISIS TAKSOMETRI Anthurium SCHOTT (ARACEAE) - Muhammad Falah; Pudji Widodo; Hexa Apriliana Hidayah (Fakultas Biologi | Universitas Jenderal Soedirman, 2014)
Anthurium Schott is one of the commercial ornamental plants in Indonesia. This genus has a high morphological variation amongst its species. This study aims to determine the similarity relationship amongst Anthurium based on morphological characters including stems, leaves, and inflorescences. This study was carried out from June to July 2012 in several locations in Purwokerto and Baturraden area, and Balai Benih Tanaman Pangan dan Hortikultura (B2TPH) Banyumas Regency. This study used explorative method with purposive random sampling. The results of the analysis using the UPGMA (Unweighted Pair Group Method with Arithmetic Mean) showed that there were 17 taxa which can be classified into 4 groups. Group I consisted of A. andraeanum “Renoir Pink”, A. andraeanum “Safari”, A. andraeanum “White”, A. andraeanum “Tropical”, A. andraeanum “cv. 1”, A. andraeanum “Amigo”, and A. nymphaeifolium. Group II consisted of A. pedatoradiatum ssp. helleborifolium, A. crystallinum, A. andicola “Kuku Bima” and A. andicola “Red List”. Group III consisted of A. crassinervium “Crispimarginatum” and A. plowmanii. Group IV consisted of A. hookeri “Garuda”, A. hookeri “Red Hookeri”, A. bonplandii ssp. guayanum, and A. jenmanii. Group I was the sister group of Group II, as well as Group III to Group IV. The closest similarity relationship was between A. andraeanum “Renoir Pink” and A. andraeanum “Safari”, whereas the farthest one was between A. bonplandii ssp. guayanum and A. andraeanum “Tropical”.